The methods of Tsarist colonial policy in Chechnya in the 18th and 19th centuries - Djamoukhanov, Faisoulkhan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
The current research looks into the history of the colonial wars of Tsarist Russia in the Caucasus during the 18th and 19th centuries and the methods of its policy. Numerous works by Western and Russian scholars have been reviewed. Mainly, such works confine themselves exclusively to the description of the wars of the Tsarist Empire, their goals and aspirations in conquering the Caucasus. However, there are questions which have not been properly answered in the works of these historians. In my view, the characters of the colonial wars of Russia and their ideological direction have not been fully analyzed. Highlighting these issues gives a distinctively new understanding of the history of Russian wars waged in the course of a few centuries. Second, but an equally important question which requires careful attention of the researcher are the methods of warfare that Russians had always conducted with their inherent cruelty. Russian colonial wars had their own peculiarities which set them apart from the rest, even from the most ruthless wars ever undertaken by Europeans. The general features that define the character of almost all colonial wars were capturing territories and establishing on them occupation regimes, which was always followed by exploitation of the land and plundering of its resources. Russians somehow differed. For them, the top priority and one of the most important tasks was the imposition of Russian mentality and Russian way of life on the subjugated nations, regardless of their religious diversity and ethnic culture traditionally formed in their centuries-old development. This policy would come into effect as soon as new territories were seized. One of the main features in their policy was suppression of any form of individuality, cynical mockery of sacred places and the way of life of the subjugated people. Russians themselves called such wars and conquests progressive because they were undertaken in the name of European civilization. In researching the history of the colonial wars of Tsarist Russia during the 16th to the 19th centuries, I have come to a final conclusion that the entire colonial policy was at its core an anti-Islamic policy since it was pursued for conquering Muslim lands, eradicating Islam as a religion and exterminating Muslim nations. Capturing Muslim territories of Ural, the Volga region, Caucasus, Crimea and Central Asia did not stop at the colonization of these territories and the establishment of occupation government. On the contrary, the policy of expansion continued taking horrible forms of mass terror, extermination of the local people and their forced conversion to Orthodox Christianity. Thus, the geography of those wars serves as a convincing proof of such conclusion. The guiding document of their expansionist policy was the Bible in which they found moral justification for their war crimes.